2022
DOI: 10.1007/s12195-021-00716-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Regional Variations of the Interstitial Cells of Cajal in the Murine Distal Stomach Informed by Confocal Imaging and Machine Learning Methods

Abstract: Introduction-The network of Interstitial Cells of Cajal (ICC) plays a plethora of key roles in maintaining, coordinating, and regulating the contractions of the gastrointestinal (GI) smooth muscles. Several GI functional motility disorders have been associated with ICC degradation. This study extended a previously reported 2D morphological analysis and applied it to 3D spatial quantification of three different types of ICC networks in the distal stomach guided by confocal imaging and machine learning methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
(47 reference statements)
1
11
0
Order By: Relevance
“…While for the distal antrum, the shift is by 71.53°; with ICC-LM (𝜑𝜑 = 163.64°, 𝜃𝜃 = 0.90°) and ICC-CM (𝜑𝜑 = 92.11°, 𝜃𝜃 = 5.02°). The observations in this study is in good agreement with the previous study 37 , which reported the orientation of ICC-LM networks relative to ICC-CM to be 92.43 ± 18.17° in the proximal and 83.98 ± 14.54° in the distal antrum. Although the outer longitudinal coat and inner circular muscle bundles of the stomach were assumed to be orthogonal 41 , the findings presented here shows that it is possible that networks of ICC-LM and ICC-CM are not perfectly perpendicular.…”
Section: D Visualisation Of Iccsupporting
confidence: 93%
See 2 more Smart Citations
“…While for the distal antrum, the shift is by 71.53°; with ICC-LM (𝜑𝜑 = 163.64°, 𝜃𝜃 = 0.90°) and ICC-CM (𝜑𝜑 = 92.11°, 𝜃𝜃 = 5.02°). The observations in this study is in good agreement with the previous study 37 , which reported the orientation of ICC-LM networks relative to ICC-CM to be 92.43 ± 18.17° in the proximal and 83.98 ± 14.54° in the distal antrum. Although the outer longitudinal coat and inner circular muscle bundles of the stomach were assumed to be orthogonal 41 , the findings presented here shows that it is possible that networks of ICC-LM and ICC-CM are not perfectly perpendicular.…”
Section: D Visualisation Of Iccsupporting
confidence: 93%
“…Nonetheless, it is important to note that the efficiency for active SW propagation within the networks of ICC does not only depend on the mean connectivity path length, but also the overall structure and function of the network e.g., network density, volume 37 , diameter, alignment and orientation. The diameter metric formulated in this study by the application of 3D Euclidean distance transform, measures the width of 3D cellular structures in the ICC network, which may be among the contributing factors affecting SW propagation through the network.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the intricate structural arrangements and biophysical relationships of different cell sub-classes of ICC and PDGFRα + cells would need to be considered across extended spatial scales. This is a challenging task that requires sophisticated whole-mount imaging of transgenic animals or specific labelling of ICC sub-types accompanied by investigations of specific channels and channel control mechanisms [62].…”
Section: Discussionmentioning
confidence: 99%
“…Disorders of gastric function that are common, but often poorly treated by available therapies, include the related conditions, gastroparesis and functional dyspepsia 1,2 . In response to the shortcomings of current treatments and difficulties in determining underlying causes of these disorders, as well as other disorders such as achalasia, gastric ileus and gastro‐esophageal reflux disease, a range of animal models have been used and, in addition, there has been recent development of computer‐based models and simulations of gastric function 3–7 . Although adequate modeling requires accurate, quantitative integration of knowledge of anatomy and function, this knowledge is not always used or readily accessible.…”
Section: Introductionmentioning
confidence: 99%